Pengaruh Kualitas Produk dan Inovasi Produk Kuliner Terhadap Minat Beli: Studi pada Warung Sate Tambak Segaran - Nadila Kusuma Wardani; Dea Rachma Sucita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study was conducted to determine the effect of product quality and culinary product innovation on millennials' purchasing interest, specifically for traditional gulai (a study at the Tambak Segaran satay stall). The independent variables used in this study were product quality and product innovation, and the dependent variable was purchasing interest. This study employed a quantitative approach. The sampling technique used was non-probability sampling, and the sample design used was purposeful sampling. The sample consisted of 110 potential gulai consumers at the Tambak Segaran Satay Stall. The data analysis method used in this study was SPSS. The results of this study indicate that H1, namely product quality has a significant influence on purchasing interest, is accepted. H2, namely product innovation has a significant influence on purchasing interest, is accepted.